MEMBUMIKAN KONSTITUSI DALAM RANGKA PENGUATAN SISTEM PEMERINTAHAN TERENDAH DI INDONESIA (Lex Jurnalica, 2020)
The importance of grounding the constitution in the context of strengthening the lowest government system, the intention is for a country so that every citizen understands his rights and responsibilities from the central level to the lowest level, namely the village. The existence of a very clear government structure as the basis of self governing community is a community that organizes itself like a village as the lowest order of government system. This paper will look at the position of the lowest government in the constitution and strengthening the lowest government system in Indonesia as the constitutional mandate. The method used is a normative legal research method. Article 18B paragraph (1) and paragraph (2) of the 1945 Constitution states that the State recognizes and respects special regional government units that are regulated by law. The state recognizes and respects the customary law community units and their traditional rights as long as they are still alive and in accordance with the development of the community and the principles of the Unitary State of the Republic of Indonesia as stipulated in the law. After 12 years of amendment to the 1945 Constitution, a village law was formed, namely Law No. 6 of 2014 concerning Villages and came into force in 2015. Strengthening the lowest system of government in Indonesia is necessary, as mandated by the constitution of the Republic of Indonesia. Considering the reform of the village government law is the mandate of the 1945 Constitution opening up opportunities for more independent villages. The village government obtains direct authority from the central government, therefore village laws as constitutional orders are separate from local government laws. The mandate of Article 18B gives legal certainty to the position of the village government and reinforces village autonomy.